Analisis Keterampilan Shooting Sepak Bola Pada Siswa Kelas V SD Negeri 2 Betung Kecamatan Betung - Suharman Suharman; Farizal Imansyah; Rury Rizhardi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Analyze the soccer shooting skills of fifth grade students at SD Negeri 2 Betung, Betung District. The method used in this research is a quantitative descriptive method in which the researcher conducted a survey using a shooting skills test technique which refers to the assessment instrument in the Learning Implementation Plan which refers to the minimum completeness of learning that has been developed. Based on data from research on soccer shooting skills in class V students at SD Negeri 2 Betung, Betung sub-district, totaling 31 children consisting of 17 girls and 14 boys. Based on the research results, it can be analyzed that the soccer shooting skills of class V students at SD Negeri 2 Betung, Betung District are in the category "Very poor at 0%, less at 22.6% (7 people), quite at 58.0% (18 people) , good 16.1% (5 people) and very 3.20% (1 person). From the average score for soccer shooting skills for class V students at SD Negeri 2 Betung, Betung sub-district, it is 50.8 and of course this score is very far below the KKM or has not yet completed the learning achievements with the description of the score being "sufficient" and still needs guidance